2022
DOI: 10.1038/s41598-022-05291-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of adolescents’ smartphone use and well-being are positive but ephemeral

Abstract: Well-being and smartphone use are thought to influence each other. However, previous studies mainly focused on one direction (looking at the effects of smartphone use on well-being) and considered between-person effects, with self-reported measures of smartphone use. By using 2548 assessments of well-being and trace data of smartphone use collected for 45 consecutive days in 82 adolescent participants (Mage = 13.47, SDage = 1.62, 54% females), the present study disentangled the reciprocal and individual dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 92 publications
2
23
0
Order By: Relevance
“…EMAs aim to minimize retrospective recall biases of traditional survey methods ( Torous et al, 2014 ), maximize ecological validity ( Russell and Gajos, 2020 ) by capturing human behavior in natural contexts, and study microprocesses ( Shiffman et al, 2008 ) in real-time. Additionally, both trace data and EMAs, or their combination ( Marciano et al, 2022 ), enable to model changes that happen at the individual level, thus allowing to overcome the Simpson’s paradox, for which the sign of a relationship observed in a population could become the opposite within the individuals ( Kievit et al, 2013 ).…”
Section: Mobile Approaches To Passively and Actively Collect Datamentioning
confidence: 99%
“…EMAs aim to minimize retrospective recall biases of traditional survey methods ( Torous et al, 2014 ), maximize ecological validity ( Russell and Gajos, 2020 ) by capturing human behavior in natural contexts, and study microprocesses ( Shiffman et al, 2008 ) in real-time. Additionally, both trace data and EMAs, or their combination ( Marciano et al, 2022 ), enable to model changes that happen at the individual level, thus allowing to overcome the Simpson’s paradox, for which the sign of a relationship observed in a population could become the opposite within the individuals ( Kievit et al, 2013 ).…”
Section: Mobile Approaches To Passively and Actively Collect Datamentioning
confidence: 99%
“…Besides investigating how personality manifests in smartphone-mediated daily behaviors, researchers have also been interested how smartphone use is related, for example, to affective well-being. Marciano et al (2022) looked for reciprocal dynamics between the frequency of smartphone use and time spent on the device and adolescents' self-reported daily well-being over 45 days. They found, among other things, that more frequent and longer smartphone use was related to higher well-being and that higher levels of well-being, in turn, were associated with longer subsequent smartphone use.…”
Section: Daily Behaviorsmentioning
confidence: 99%
“…They found, among other things, that more frequent and longer smartphone use was related to higher well-being and that higher levels of well-being, in turn, were associated with longer subsequent smartphone use. Comparing changes in affective well-being with changes in frequency and duration of smartphone use, they found that the former lasted longer (Marciano et al, 2022).…”
Section: Daily Behaviorsmentioning
confidence: 99%
“…In the past few years, several research groups have tried to resolve the inconsistency in the social media well-being literature by adopting a person-specific or idiographic media effects approach (Griffioen et al, 2021;Marciano et al, 2022;). An idiographic media effects approach involves the in-depth understanding of the effects of (social) media use on each single person.…”
Section: Affects Themmentioning
confidence: 99%